Arthroscopic treatment of anteromedial ankle impingement - Arrondo, Guillermo; Gómez, Daniel; Matías-Joannas, Germán; Martín-Oliva, Xavier; Iglesias, Matías; Casola, Leandro (Journal of the Foot & Ankle, 2020)
Objective: Impingement syndromes are recognized as an important cause of chronic ankle pain, which results from the entrapment of an inflamed soft-tissue component between the osteophytes. The predominant site of occurrence is the anterolateral aspect of the ankle for soft-tissue impingement, and anteromedial aspect for bony impingement. Symptoms related to the physical impact of bone or soft-tissue pain often result in limited ankle range of motion. Methods: We conducted a retrospective study of 34 patients (34 ankles) with anteromedial bony impingement. All patients underwent arthroscopy, with a mean follow-up of 34 months. Results: All osteophytes were removed, and the ankle range of motion improved. The AOFAS score improved from 73 preoperatively to 95 postoperatively. Conclusion: The arthroscopic removal of the anteromedial osteophytes of the ankle had excellent functional results. It is an effective procedure that allows rapid patient recovery. Level of Evidence IV; Therapeutic Studies; Case Series.